Avaliação do perfil da resposta imune por meio do receptor Dectina-1 na esporotriose murina - Jellmayer, Juliana Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Sporotrichosis is a worldwide distributed mycosis caused by thermodimorphic fungi from the Sporothrix schenckii species complex. The disease's most common form is the lymphocutaneous, which compromises the skin, subcutaneous tissue and regional lymphatic ganglia. Cells from the innate immune system recognize pathogens through pattern recognition receptors (PRRs). Among these, the toll-like (TLRs) and C-type lectin (CLRs) receptors can be highlighted for having members capable of recognizing fungal antigens. The interaction between PRRs and pathogen-associated molecular patterns (PAMPs) triggers various signaling pathways involved in modulating the following adaptive response and in potentiating the phagocytic and microbicidal capabilities of macrophages and other phagocytes. Dectin-1 is a widely expressed CLR in macrophages, dendritic cells and neutrophils, being a receptor for β-glucan implicated in the phagocytic process, the oxidative burst, and in the production of soluble mediators such as cytokines and chemokines. The present study was aimed at assessing the role of β-glucans, known Dectin-1 ligands, in the phagocytosis and production of soluble mediators, oxygen (H2O2), and nitrogen (NO) intermediates by peritoneal macrophages from Balb/c mice during infection with S. schenckii ATCC 16345. In order to do that, the macrophages were challenged with the alkali-insoluble fraction (F1) extracted from the S. schenckii cell wall, which is mainly composed of β-glucans, with a purified commercial β-1,3-glucan, or with whole heat-killed S. schenckii yeasts. Our results showed that phagocytosis of the S. schenckii yeasts, as well as production of NO, H2O2, and the cytokines IL-10, TNF-α and IL-1β occur by the recognition of both the β-glucans and other additional components found in the F1 fraction. Furthermore, Dectin-1 expression was augmented on days 10 and 15 ...

A esporotricose é uma micose de distribuição universal causada por fungos termodimórficos do complexo de espécies de Sporothrix schenckii. A forma mais comum da doença é a linfocutânea que compromete pele, tecido subcutâneo e gânglios linfáticos regionais. Células do sistema imune inato reconhecem patógenos por meio de receptores de reconhecimento de padrão (PRRs). Dentre esses, podemos destacar a família dos receptores do tipo Toll-like (TLRs) e dos receptores de lectina do tipo C (CLRs), os quais possuem membros capazes de reconhecer antígenos fúngicos. A interação entre os PRRs e os padrões moleculares associados aos patógenos (PAMPs) desencadeia uma série de vias de sinalização envolvidas na modulação da resposta adaptativa subsequente e na potencialização da capacidade fagocítica e microbicida dos macrófagos e de outros fagócitos. A Dectina-1 é um CLR amplamente expresso em macrófagos, células dendríticas e neutrófilos, sendo um receptor para β-glucana implicado no processo de fagocitose, no burst oxidativo e na produção de fatores solúveis, tais como citocinas e quimiocinas. O objetivo do presente estudo foi avaliar o papel das β-glucanas, reconhecidas ligantes de Dectina-1, na fagocitose e na produção de intermediários do oxigênio (H2O2) e nitrogênio (NO) e de mediadores solúveis por macrófagos peritoneais de camundongos Balb/c durante a infecção por S. schenckii ATCC 16345. Para tanto, os macrófagos foram desafiados com a fração álcali-insolúvel (F1) extraída da parede celular de S. schenckii, composta principalmente de β-glucanas, com uma β-1,3-glucana pura comercial ou com o fungo íntegro termo-inativado. Nossos resultados mostraram que tanto a fagocitose das leveduras de S. schenckii, como a produção de NO, H2O2 e das citocinas IL-10, TNF-α e IL-1β se dá pelo reconhecimento tanto das β-glucanas...
Keywords: Esporotricose; Peróxido de hidrogênio; Fagocitose; Oxido nítrico; Citocinas; Sporotrichosis